Needs of Children Experiencing Homelessness who are Living in Shelters: A Qualitative Investigation of Perceptions of Care Workers to Inform Music Therapy Clinical Practice - Yates, Greta Jean; Silverman, Michael Joseph (Voices: A World Forum for Music Therapy, 2016)
On a single night in January in 2014 there were 194,000 children living with their families in shelters in the United States (National Center on Family Homelessness, 2015). A typical family experiencing homelessness consists of a single mother with two to three children. Children experiencing homelessness are more likely to face academic, social, and emotional problems compared to children in poverty. As there is currently a dearth of peer reviewed publications related to music therapy with children experiencing homelessness, the purpose of this study was to explore the perceived needs of children living in a homeless shelter through interviews with care workers and apply results to the music therapy clinical practice. Participants were seven staff members employed at a shelter for women and children experiencing homelessness in the Midwestern part of the United States. Data analysis was based upon Braun and Clarke’s (2006) six phases of thematic analysis. Emerging themes included: (a) staff need to be positive role models and provide trusting and affectionate relationships, (b) older children require programming and opportunities for communication and emotional support, (c) wellbeing must be screened and monitored, and (d) routine and expectations are needed to promote a calm living environment. Implications for music therapy clinical practice, limitations, and suggestions for future research concerning music therapy with children experiencing homelessness are provided.